THE IMPACT OF WORK-LIFE BALANCE ON EMPLOYEE PERFORMANCE AND RETENTION: A META-ANALYTIC ANALYSIS OF EMPIRICAL STUDIES - Eloh Bahiroh; Sri Ndaru Arthawati (ADISAM Publisher, 2024)
The relationship between work-life balance, employee performance, and retention is an area of great importance to researchers and practitioners in the domain of organisational behaviour. This literature review is to measure the impact of work-life balance on employee performance and retention. The results of this study indicate suggest that organisations that invest in work-life balance practices can expect to see better employee outcomes and a competitive advantage in talent management. The study also identifies gaps in the current literature and recommends directions for future research, emphasising the need for longitudinal studies and consideration of moderating variables such as gender, age, and cultural differences. The results of this study have practical implications for human resource policy, emphasising the need for companies to adopt comprehensive work-life balance programmes to improve employee well-being, organisational commitment, and performance.